1994
DOI: 10.1097/00132586-199404000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Long Term Backache After Childbirth

Abstract: and suggests that antenatal testing could prevent a significant proportion ofvertical infection.In a recent survey of all obstetric units in the British Isles, 51% were offering HIV tests only to women perceived as being at risk, 3% to all women, and the remainder had no formal policy.3 Our results show that in south east England, only 17% of live births to infected women are recognised before delivery. There is therefore considerable scope for improvement in antenatal HIV testing programmes.We thank the obste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 0 publications
3
44
1
Order By: Relevance
“…The issue has drawn a significant amount of attention in the literature. Of the two authors who found epidural anaesthesia to be a risk factor, one [95] later came to the conclusion that the relationship between epidural anaesthesia and subsequent lumbopelvic pain did not exist [93], while the other [53] persisted [54]. The conflict can be resolved if one considers the statistical principles involved.…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The issue has drawn a significant amount of attention in the literature. Of the two authors who found epidural anaesthesia to be a risk factor, one [95] later came to the conclusion that the relationship between epidural anaesthesia and subsequent lumbopelvic pain did not exist [93], while the other [53] persisted [54]. The conflict can be resolved if one considers the statistical principles involved.…”
Section: Risk Factorsmentioning
confidence: 99%
“…With respect to the risk-factors literature, evidence was conflicting. In two studies [95,97], no effect of ethnicity was found, but in others, prevalence was reported to be relatively high in Caucasians [31], in women of Sephardic origin [78], or Asians [53]. Given our analysis of prevalence during pregnancy, and the fact that pregnancy-related lumbopelvic pain has been reported from many countries-in Africa [9,76,110], the Americas [27,31], Asia [35,70,104,109], Australia [16], and Europe [2,28,59,68,85,88, 100]-we propose concluding that the few cases in which a relationship was found occurred by chance, and that, actually, maternal ethnicity is not a risk factor.…”
Section: Risk Factorsmentioning
confidence: 99%
“…The incidence of back pain after epidural anesthesia has been observed to be between 18 and 19% in rich retrospective studies (48,49,51) and between 21 and 53% in prospective studies (50, 51)…”
Section: Nerve and Root Injurymentioning
confidence: 99%
“…1 They ignore evidence from previous studies that shows the substantial advantage of serum screening over screening based on maternal age alone. [2][3][4] Their view is based on the results from two districts, the only two out of the eight where serum screening was routinely offered (using the Double test).…”
Section: Audit Of Down's Syndrome Screening Is Not Validmentioning
confidence: 99%
“…1 2 Stevenson and Whitehead in the BMJ said that the increased risk of breast cancer in the study was small, but they did not mention that during the study 42% of women taking active drug and 38% receiving placebo stopped the assigned treatment. 1 In 2 Stevenson and Whitehead deduced that because the risk of breast cancer was not appreciably increased in the first few years of taking hormone replacement therapy, women wishing to take short courses of this form of hormone replacement should be reassured. There must, however, be an interval between applying an agent that increases breast cancer development and the cancer manifesting clinically, so the validity of their deduction is open to question.…”
Section: Message About Hormone Replacement Therapy Is Unclearmentioning
confidence: 99%